The Accountant Satisfaction in Using ERP Systems - Weli Weli (CommIT (Communication and Information Technology) Journal, 2018)
Although studies of the benefits of Enterprise Resource Planning (ERP) have been done before, the analysis of accountant satisfaction models in using ERP systems has not been explored specifically from the perceptions of accounting benefits, operational benefits, individual productivity, and managerial benefits. There has been significant growth in the use of ERP systems in Indonesia. Therefore, this study proposes a model of the accountant satisfaction in using the ERP systems. The population of this study is the accountants working in Jakarta. The data are collected from ERP users in several companies in Jakarta by using a questionnaire with snowball sampling method. As much as 282 respondents return the questionnaire. The analysis of the proposed model is done by Partial Least Square (PLS). The results of the analysis provide support to the proposed model that accounting benefits, operational benefits, individual productivity, and managerial benefits are indicators that measure user satisfaction of ERP systems. The expected theoretical contribution of the results of this study is to provide insight into the system user satisfaction model, apart from the practical contribution for ERP provider companies for paying attention to the factors affecting ERP user satisfaction.